Statististics for Business and Economics (Delhi Cengage Learning, 2011)
Applications of data analysis and statistical methodology are an integral part of the organization and presentation of the text material. Contents:- 1.Data and Statistics, 2. Descriptive Statistics: Tabular and Graphical Presentations,3.Descriptive Statistics: Numerical Measures,4. Introduction to Probability,5.Discrete Probability Distributions, 6. Continuous Probability Distributions, 7. Sampling and Sampling Distributions
Keywords: Statistics for Business and Economics; MANAGEMENT STATISTICS -(F-40)